Preparation method and application of a carbon-supported FeCo diatomic porous lithium-sulfur battery composite material

Carbon-supported FeCo diatomic porous lithium-sulfur battery composite materials are prepared through Joule heat treatment technology, which solves the problems of single metal site limitation and low preparation efficiency of diatomic composite materials, and achieves high specific capacity and improved rate performance of lithium-sulfur batteries.

CN118825243BActive Publication Date: 2025-01-24SHANDONG HAIHUA GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411264335.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-24
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The end-face adsorption structure of single metal sites in lithium-sulfur batteries leads to the limitation of the adsorption capacity and catalytic activity of single-atom composite materials, and the preparation efficiency of diatom composite materials is inefficient and costly.

Method used

Use coke ear heat treatment technology to prepare carbon loaded Feco bisod-porous lithium-sulfur battery composite materials, generate Feco-ZIF-8 through Fecozn-O nanoparticles and 2-methamidazole reactions, and heat treatment in the coke ear heating device to obtain. Class hole structure and composite material for carbon defects.

Benefits of technology

It accelerates the conversion reaction kinetics of polysulfides, promotes the deposition of lithium sulfide, improves the specific capacity and rate performance of lithium-sulfur batteries, and has high preparation efficiency and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118825243B_ABST
    Figure CN118825243B_ABST
Patent Text Reader

Abstract

The present invention provides a preparation method and application of a carbon-supported FeCo diatomic porous lithium-sulfur battery composite material, and belongs to the technical field of preparation of positive electrode materials for lithium-sulfur batteries. The present invention uses FeCoZn-O nanoparticles as raw materials and reacts with dimethylimidazole to generate FeCo-ZIF-8 in situ. Among them, the Co element mainly replaces the site of Zn and coordinates with nitrogen, while the Fe element is mainly combined with oxygen and dispersed in ZIF-8. Due to the different coordination environments of the two elements Fe and Co and the uniform dispersion in the entire material, FeCo-ZIF-8 can be quickly prepared into a carbon-supported FeCo diatomic porous lithium-sulfur battery composite material through Joule heat treatment technology, which significantly enhances the interaction between polysulfides and active sites, thereby accelerating the conversion reaction kinetics of polysulfides and promoting the deposition of lithium sulfide, thereby improving the specific capacity and rate performance of lithium-sulfur batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a carbon-supported FeCo diatomic porous lithium-sulfur battery composite material, belonging to the technical field of preparation of lithium-sulfur battery positive electrode materials. Background Art

[0002] Lithium-sulfur batteries are considered to be one of the most promising next-generation energy storage systems due to their high theoretical capacity, abundant resources, and environmental friendliness. However, the insulating properties of elemental sulfur, the severe shuttle effect of polysulfides, the high reaction energy barrier, and the slow redox reaction kinetics limit the actual capacity and long-term stability of lithium-sulfur batteries, hindering the commercial development of lithium-sulfur batteries. In recent years, researchers have conducted extensive exploration of the main cathode materials of lithium-sulfur batteries, mostly by increasing the sulfur content in the materials to improve the electrochemical performance, but this will sacrifice the overall energy density of lithium-sulfur batteries and also limit the redox kinetics of polysulfides.

[0003] Carbon-supported single-atom composites are expected to solve the problems of shuttle effect and slow redox reaction due to their unique electronic structure, high catalytic activity and maximum atomic utilization, and have become ideal materials for lithium-sulfur batteries. However, the end-face adsorption structure between the single metal site and the polysulfide limits the adsorption capacity and catalytic activity of the single-atom composites. In order to meet these challenges, carbon-supported double single-atom composites construct double metal active sites to optimize the adsorption and desorption capacity of the catalytic sites, thereby achieving higher metal loading and more flexible active site structure. At present, the preparation of carbon-supported double-atom composites mostly needs to be prepared by high-temperature pyrolysis or chemical vapor deposition in a tubular furnace. This involves a tubular furnace or a chemical vapor deposition furnace, both of which have slow heating and cooling rates, consuming a lot of time, electricity and gas. At the same time, due to the long calcination time, it is more likely to cause sintering of the carbon base material, agglomeration of metal atoms and other problems.

[0004] The Chinese invention patent with the publication number CN116960323A discloses a FeCo double single atom modified nitrogen-doped porous carbon fiber and its preparation method and a lithium-sulfur battery. The method synthesizes a nano Zn-triazole metal organic framework material (MET-6) by zinc chloride and H-1,2,3-triazole, and then MET-6 is subjected to cation exchange with Co and Fe to obtain FeCo-doped MET-6. The FeCo-doped MET-6 and polyacrylonitrile are prepared by electrospinning technology to obtain a precursor (tubular nanofiber morphology); the precursor is calcined at a high temperature of 500-1200°C for 4-10h to obtain FeCo double single atom modified nitrogen-doped porous carbon fiber. In this preparation method, due to the use of the traditional tubular furnace calcination method, it is easy to cause the collapse of the pore structure (the pore size becomes smaller) and the agglomeration of metal atoms. In addition, by adding polyacrylonitrile, not only more carbon sources can be introduced, but also materials with tubular morphology can be obtained, but this method does not require the introduction of additional carbon sources.

[0005] The Chinese invention patent with publication number CN113054183A discloses a method for preparing a CoNi bimetallic organic framework-derived carbon-sulfur composite material. The method first synthesizes a CoNi bimetallic organic framework (MOF) material, and then calcines it in a tubular furnace to obtain a CoNi bimetallic MOF-derived carbon material. It can be seen from the specific surface area diagram of the patent that the adsorption curve belongs to a type II adsorption curve, indicating that the material is a macroporous material and does not belong to a multi-level pore structure material rich in mesopores; in addition, the use of traditional tubular furnace calcination methods is prone to cause pore structure collapse (pore size reduction) and metal atom agglomeration, resulting in a decrease in electrochemical performance.

[0006] The Chinese invention patent with publication number CN116960331A discloses a method for preparing a sulfurized polyacrylonitrile positive electrode material for lithium-sulfur batteries. The method is to react a variety of metal salts with organic ligands to obtain a precursor, and then place the precursor in a tubular furnace for calcination, and then acid-etch to obtain a target product, and finally the target product and sulfur powder and polyacrylonitrile are subjected to secondary calcination in a tubular furnace to obtain a positive electrode material. The preparation of this method is cumbersome, and not only secondary calcination but also acid treatment is required; wherein secondary calcination will increase energy consumption, and although acid treatment will etch the material to obtain a wider pore range, the waste acid generated will cause environmental pollution. In addition, the addition of polyacrylonitrile is to introduce more carbon sources and increase its conductivity, but this method does not require additional carbon sources. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing a carbon-supported FeCo diatomic porous lithium-sulfur battery composite material, which can solve the problem that the end-face adsorption structure of a single metal site in a lithium-sulfur battery leads to limited adsorption capacity and catalytic activity of the single-atom composite material, as well as the problem that the preparation efficiency of the diatomic composite material is low and the cost is high. The method accelerates the conversion reaction kinetics of polysulfide and promotes the deposition of lithium sulfide, thereby improving the specific capacity and rate performance of the lithium-sulfur battery.

[0008] To achieve this object, the technical solution of the present invention is:

[0009] A method for preparing a carbon-supported FeCo diatomic porous lithium-sulfur battery composite material comprises the following steps:

[0010] (1) adding zinc acetate, cobalt acetate and ferric acetate into dimethyl sulfoxide to dissolve to obtain a first mixed solution; adding tetramethylammonium hydroxide into ethanol to dissolve to obtain a second mixed solution;

[0011] (2) under stirring, the second mixed solution is added dropwise to the first mixed solution, after the dropwise addition is completed, the mixture is stirred at room temperature for 5-10 minutes to obtain a third mixed solution; ethyl acetate is added to the third mixed solution, and the mixture is centrifuged and vacuum dried to obtain FeCoZn-O nanoparticles;

[0012] (3) preparing a mixed solvent of methanol and water, then adding FeCoZn-O nanoparticles and 2-methylimidazole into the mixed solvent, stirring and reacting at 40-80°C for 10-20h, centrifuging, washing, and vacuum drying to obtain FeCo-ZIF-8;

[0013] (4) FeCo-ZIF-8 is placed in the groove of the graphite sample stage of a Joule heating device, and then Joule heat treatment is performed under a protective atmosphere of nitrogen or argon to obtain a carbon-supported FeCo diatomic porous lithium-sulfur battery composite material.

[0014] Furthermore, in the step (1), the ratio of zinc acetate, cobalt acetate, iron acetate and dimethyl sulfoxide in the first mixed solution is: 1mmol: 0.02-0.04mmol: 0.03-0.06mmol: 20-30mL; the ratio of tetramethylammonium hydroxide and ethanol in the second mixed solution is 4-8mmol: 20mL.

[0015] Furthermore, in the step (2), the stirring speed is 100-300 r / min; the dropping time is 1-3 h; and the vacuum drying conditions are: drying temperature 50-80° C., and drying time 18-24 h.

[0016] Furthermore, in step (2), the volume ratio of ethyl acetate to the total solvent of dimethyl sulfoxide and ethanol in the third mixed solution is 0.4-0.6:1.

[0017] Furthermore, in step (3), the volume ratio of methanol to water in the mixed solvent is 1 mL:0.2-1 mL; the dosage ratio of FeCoZn-O nanoparticles, 2-methylimidazole, and the mixed solvent is 0.1 g:0.5-2 g:24-50 mL.

[0018] Furthermore, in step (3), the washing conditions are: washing with deionized water and methanol three to five times respectively; and the vacuum drying conditions are: drying temperature 50-80° C., and drying time 5-10 h.

[0019] Furthermore, in step (4), the conditions of the Joule heat treatment are: heat treatment temperature 700-1500°C, heating rate 1000-2500°C / s, and Joule heat treatment times 2-10 times. The Joule heat treatment is heating from room temperature to the target temperature, and then naturally cooling to room temperature, which is represented as one time.

[0020] Another object of the present invention is to provide an application of the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material prepared by the above method, which is applied to the positive electrode of a lithium-sulfur battery.

[0021] The beneficial effects of the present invention are:

[0022] (1) Compared with the traditional calcination method, the Joule heat treatment technology of the present invention has simple equipment operation, high preparation efficiency and low energy consumption. The rapid heating and cooling characteristics of the Joule heat treatment technology are conducive to the pyrolysis of the ligand to produce a large number of carbon defects and multi-level pore structures, providing more sites for anchoring metal atoms.

[0023] (2) The present invention uses FeCoZn-O nanoparticles as raw materials and reacts with 2-methylimidazole to generate FeCo-ZIF-8 in situ. Among them, the Co element mainly replaces the Zn site and coordinates with nitrogen, while the Fe element is mainly combined with oxygen and dispersed in ZIF-8. It is precisely because of the different coordination environments of the two elements Fe and Co and the uniform dispersion in the entire material that FeCo-ZIF-8 can be quickly prepared into a carbon-supported FeCo diatomic porous lithium-sulfur battery composite material with uniform element dispersion through Joule heat treatment technology. At the same time, the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material as the positive electrode of the lithium-sulfur battery stimulates the synergistic effect between Fe and Co atoms, thereby significantly enhancing the interaction between polysulfides and active sites, thereby accelerating the conversion reaction kinetics of polysulfides and promoting the deposition of lithium sulfide, thereby improving the specific capacity and rate performance of the lithium-sulfur battery.

[0024] (3) The carbon-supported FeCo diatomic porous lithium-sulfur battery composite material prepared by the present invention has a multi-level porous structure of mesopores and macropores with a pore size range of 3-62nm, and its carbon defects (I D / I G ) content is 0.73-0.83, and it has outstanding performance in the positive electrode of lithium-sulfur batteries. At a high rate of 1C, the initial specific capacity of the lithium-sulfur battery is as high as 818.52-1048.49mAh / g, and after 700 cycles, the capacity retention rate is 73.54-77.47%; at a high rate of 5C, the initial specific capacity is as high as 518.8-732.5mAh / g, and the recovery rate from 5C to 0.2C is 93.51-96.02%. Therefore, the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material exhibits excellent high-rate capacity, high stability, high rate, and reversibility in the lithium-sulfur battery reaction, and has broad prospects for industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The Raman spectra of the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material obtained in step (4) of Example 1 and Comparative Example 1;

[0026] Figure 2 This is a spherical aberration corrected high-angle annular dark field scanning transmission electron microscopy image of the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material obtained in step (4) of Example 1;

[0027] Figure 3 This is a test graph of the electrochemical long cycle performance of a lithium-sulfur battery positive electrode prepared from the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material obtained in step (4) of Example 1 at a rate of 1C;

[0028] Figure 4 This is a high rate test diagram of a lithium-sulfur battery positive electrode prepared from the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material obtained in step (4) of Example 1 at 0.2-5C. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that a person skilled in the art can better understand and implement the present invention, but the protection scope of the present invention is not limited thereto.

[0030] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available materials; unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those generally understood by those skilled in the art.

[0031] In each embodiment of the specific implementation of the present invention, the Joule heating device used is composed of a gas circuit device, a vacuum pump, a graphite sample stage, a temperature control system, and a data acquisition system. The model is CIS-JH3.3-P, the output voltage is 0-40V, the output current is 0-500A, the temperature measurement range is 0-3000℃, the power supply is 380V / 30A, and the current ramp time is 1ms. Example 1

[0032] (1) 1 mmol zinc acetate, 0.03 mmol cobalt acetate, and 0.04 mmol ferric acetate were added to 25 mL dimethyl sulfoxide and dissolved by ultrasonication to obtain a first mixed solution; 6 mmol tetramethylammonium hydroxide was added to 20 mL ethanol and dissolved by ultrasonication to obtain a second mixed solution;

[0033] (2) under stirring at a speed of 200 r / min, the second mixed solution was added dropwise to the first mixed solution, the addition time was 2 h, and the stirring reaction was continued at 200 r / min at room temperature for 8 min to obtain a third mixed solution; 22.5 mL of ethyl acetate was added to the third mixed solution, and the mixture was centrifuged and vacuum dried at 65 ° C for 22 h to obtain FeCoZn-O nanoparticles;

[0034] (3) 20 mL of methanol and 16 mL of water were prepared into a mixed solvent, and then 0.1 g of FeCoZn-O nanoparticles and 1 g of 2-methylimidazole were added to the mixed solvent, and then stirred at 60 °C for 15 h. The mixture was centrifuged, washed four times with deionized water and methanol, and dried in vacuum at 65 °C for 8 h to obtain FeCo-ZIF-8.

[0035] (4) FeCo-ZIF-8 was placed in the groove of the graphite sample stage of the Joule heating device, and then Joule heat treatment was performed 6 times under a nitrogen protective atmosphere. The Joule heat treatment temperature was 1100°C and the Joule heat treatment heating rate was 1500°C / s to obtain a carbon-supported FeCo diatomic porous lithium-sulfur battery composite material.

[0036] The carbon-supported FeCo diatomic porous lithium-sulfur battery composite material obtained in step (4) was subjected to Raman spectroscopy test, spherical aberration corrected high-angle annular dark field scanning transmission electron microscopy test, and nitrogen total adsorption (N2-BET) pore size distribution test, respectively. Figure 1 , Figure 2 , Table 1, where the pore size distribution test results of N2-BET are the full-pore pore size distribution based on the NLDFT model.

[0037] Depend on Figure 1 It can be seen that I D / I G The ratio is the D band (1353 cm-1 peaks around 1587 cm) and ordered sp2 hybridized carbon G band (1587 cm -1 ) peak area ratio, the I D / I G The value of I is 0.82. D / I G It is much larger than 0.6 of conventional materials, indicating that the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material has a rich carbon defect structure; Figure 2 It can be seen that Fe and Co diatoms are well dispersed on the carbon material substrate. When the bright spots are not aggregated, they are separated bright spots, indicating that the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material has good dispersibility. As shown in Table 1, the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material has a multi-level pore structure with rich mesopores and macropores, and the pore size range is 4-62nm, which is conducive to the adsorption of polysulfides.

[0038] The carbon-supported FeCo diatomic porous lithium-sulfur battery composite material obtained in step (4) is used for lithium-sulfur battery testing, including the following application steps:

[0039] ① The carbon-supported FeCo diatomic porous lithium-sulfur battery composite material and sublimated sulfur were mixed in a mass ratio of 1:3 and loaded into a reactor lined with polytetrafluoroethylene, and heated at 160°C for 16 hours to solidify the sulfur, thereby obtaining a solidified positive electrode material;

[0040] ②In an inert atmosphere glove box, the solid sulfur positive electrode material, polypropylene porous membrane separator and electrolyte (a mixed solution of 1 mol / L lithium bis(trifluoromethanesulfonyl)imide and 0.2 mol / L lithium nitrate with 1,3-dioxolane and 1,2-dimethoxyethane (the volume ratio of 1,3-dioxolane to 1,2-dimethoxyethane is 1:1)) are assembled into a button battery. The battery is tested for electrochemical long cycle performance at 1C rate and high rate test at 0.2-5C on the CT-4008-5A6V system. The test results are shown in Figure 3 and Figure 4 .

[0041] Depend on Figure 3 It can be seen that the first-cycle discharge capacity at a rate of 1C is 1048.49 mAh / g. After 700 cycles, the capacity remains at 812.26 mAh / g. The average capacity decay rate per cycle is 0.032%, and the capacity retention rate is 77.47%. It has good initial specific capacity, cycle stability and high capacity decay rate.

[0042] Depend on Figure 4It can be seen that at the charge and discharge rate of 0.2-5C, the capacity reached 1250.29mAh / g and 732.5mAh / g at 0.2C and 5C respectively. When switched to 0.2C, the capacity reached 1200.52mAh / g, and the recovery rate reached 96.02%, indicating that it has highly reversible electrochemical properties and exhibits good rate performance. Example 2

[0043] (1) 1 mmol zinc acetate, 0.02 mmol cobalt acetate, and 0.03 mmol ferric acetate were added to 20 mL dimethyl sulfoxide and dissolved by ultrasonication to obtain a first mixed solution; 4 mmol tetramethylammonium hydroxide was added to 20 mL ethanol and dissolved by ultrasonication to obtain a second mixed solution;

[0044] (2) under stirring at a speed of 100 r / min, the second mixed solution was added dropwise to the first mixed solution, the addition time was 1 hour, and the stirring reaction was continued at 100 r / min at room temperature for 10 minutes to obtain a third mixed solution; 16 mL of ethyl acetate was added to the third mixed solution, and the mixture was centrifuged and vacuum dried at 50°C for 24 hours to obtain FeCoZn-O nanoparticles;

[0045] (3) 20 mL of methanol and 4 mL of water were prepared into a mixed solvent, and then 0.1 g of FeCoZn-O nanoparticles and 0.5 g of 2-methylimidazole were added to the mixed solvent, and then stirred at 40 °C for 20 h. The mixture was centrifuged, washed three times with deionized water and methanol, and dried under vacuum at 50 °C for 10 h to obtain FeCo-ZIF-8.

[0046] (4) FeCo-ZIF-8 was placed in the groove of the graphite sample stage of the Joule heating device, and then Joule heat treatment was performed twice under a nitrogen protective atmosphere at a Joule heat treatment temperature of 1500°C and a Joule heat treatment heating rate of 1000°C / s to obtain a carbon-supported FeCo diatomic porous lithium-sulfur battery composite material.

[0047] The carbon-supported FeCo diatomic porous lithium-sulfur battery composite material obtained in step (4) was subjected to Raman spectroscopy test and N2-BET pore size distribution test, and the test results are shown in Table 1.

[0048] As shown in Table 1, the I D / I G The value of I is 0.73, D / I GIt is much larger than 0.6 of conventional materials, indicating that the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material has a rich carbon defect structure; the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material has a multi-level pore structure with rich mesopores and macropores, with a pore size range of 3-51nm, which is conducive to the adsorption of polysulfides.

[0049] The carbon-supported FeCo diatomic porous lithium-sulfur battery composite material obtained in step (4) was used for lithium-sulfur battery testing. The testing method was the same as Example 1. The test results are shown in Table 1.

[0050] As can be seen from Table 1, the first-cycle discharge capacity at a rate of 1C is 818.52 mAh / g. After 700 cycles, the capacity retention rate is 73.54%, which has good initial specific capacity, cycle stability and high capacity attenuation rate; at a high charge and discharge rate of 0.2-5C, the initial specific capacity at a rate of 5C is 518.8 mAh / g, and the capacity recovery rate reaches 93.51% when switched to 0.2C, indicating highly reversible electrochemical properties and showing good rate performance. Example 3

[0051] (1) 1 mmol zinc acetate, 0.04 mmol cobalt acetate, and 0.06 mmol ferric acetate were added to 30 mL dimethyl sulfoxide and dissolved by ultrasonication to obtain a first mixed solution; 8 mmol tetramethylammonium hydroxide was added to 20 mL ethanol and dissolved by ultrasonication to obtain a second mixed solution;

[0052] (2) under stirring at a speed of 300 r / min, the second mixed solution was added dropwise to the first mixed solution, the addition time was 3 h, and the stirring reaction was continued at 300 r / min at room temperature for 5 min to obtain a third mixed solution; 30 mL of ethyl acetate was added to the third mixed solution, and the mixture was centrifuged and vacuum dried at 80°C for 18 h to obtain FeCoZn-O nanoparticles;

[0053] (3) 25 mL of methanol and 25 mL of water were prepared into a mixed solvent, and then 0.1 g of FeCoZn-O nanoparticles and 2 g of 2-methylimidazole were added to the mixed solvent, and then stirred at 80 °C for 10 h. The mixture was centrifuged, washed with deionized water and methanol five times respectively, and vacuum dried at 80 °C for 5 h to obtain FeCo-ZIF-8;

[0054] (4) FeCo-ZIF-8 was placed in the groove of the graphite sample stage of the Joule heating device, and then Joule heat treatment was performed 10 times under a nitrogen protective atmosphere, with a Joule heat treatment temperature of 700°C and a Joule heat treatment heating rate of 3000°C / s to obtain a carbon-supported FeCo diatomic porous lithium-sulfur battery composite material.

[0055] The carbon-supported FeCo diatomic porous lithium-sulfur battery composite material obtained in step (4) was subjected to Raman spectroscopy test and N2-BET pore size distribution test, and the test results are shown in Table 1.

[0056] As shown in Table 1, the I D / I G The value of I is 0.78, D / I G It is much larger than 0.6 of conventional materials, indicating that the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material has a rich carbon defect structure; the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material has a multi-level pore structure with rich mesopores and macropores, with a pore size range of 5-56nm, which is conducive to the adsorption of polysulfides.

[0057] The carbon-supported FeCo diatomic porous lithium-sulfur battery composite material obtained in step (4) was used for lithium-sulfur battery testing. The testing method was the same as Example 1. The test results are shown in Table 1.

[0058] As can be seen from Table 1, the first-cycle discharge capacity at a rate of 1C is 895.62 mAh / g. After 700 cycles, the capacity retention rate is 75.58%, which has good initial specific capacity, cycle stability and high capacity attenuation rate; at a high charge and discharge rate of 0.2-5C, the initial specific capacity at a rate of 5C is 585.9 mAh / g, and the capacity recovery rate reaches 94.85% when switched to 0.2C, indicating highly reversible electrochemical properties and showing good rate performance. Example 4

[0059] (1) 1 mmol zinc acetate, 0.025 mmol cobalt acetate, and 0.045 mmol ferric acetate were added to 22 mL dimethyl sulfoxide and dissolved by ultrasonication to obtain a first mixed solution; 5.5 mmol tetramethylammonium hydroxide was added to 20 mL ethanol and dissolved by ultrasonication to obtain a second mixed solution;

[0060] (2) under stirring at a speed of 250 r / min, the second mixed solution was added dropwise to the first mixed solution, the addition time was 1.5 h, and the stirring reaction was continued at room temperature at 250 r / min for 8 min to obtain a third mixed solution; 23.1 mL of ethyl acetate was added to the third mixed solution, and the mixture was centrifuged and vacuum dried at 60°C for 22 h to obtain FeCoZn-O nanoparticles;

[0061] (3) 20 mL of methanol and 16 mL of water were prepared into a mixed solvent, and then 0.1 g of FeCoZn-O nanoparticles and 1.2 g of 2-methylimidazole were added to the mixed solvent, and then stirred at 60 °C for 15 h. The mixture was centrifuged, washed four times with deionized water and methanol, and dried in vacuum at 60 °C for 8 h to obtain FeCo-ZIF-8.

[0062] (4) FeCo-ZIF-8 was placed in the groove of the graphite sample stage of the Joule heating device, and then Joule heat treatment was performed 5 times under the protective atmosphere of argon gas. The Joule heat treatment temperature was 1000°C and the Joule heat treatment heating rate was 1800°C / s to obtain a carbon-supported FeCo diatomic porous lithium-sulfur battery composite material.

[0063] The carbon-supported FeCo diatomic porous lithium-sulfur battery composite material obtained in step (4) was subjected to Raman spectroscopy test and N2-BET pore size distribution test, and the test results are shown in Table 1.

[0064] As shown in Table 1, the I D / I G The value of I is 0.80, D / I G It is much larger than 0.6 of conventional materials, indicating that the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material has a rich carbon defect structure; the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material has a multi-level pore structure with rich mesopores and macropores, with a pore size range of 5-58nm, which is conducive to the adsorption of polysulfides.

[0065] The carbon-supported FeCo diatomic porous lithium-sulfur battery composite material obtained in step (4) was used for lithium-sulfur battery testing. The testing method was the same as Example 1. The test results are shown in Table 1.

[0066] As can be seen from Table 1, the first-cycle discharge capacity at a rate of 1C is 937.83 mAh / g. After 700 cycles, the capacity retention rate is 76.35%, which has good initial specific capacity, cycle stability and high capacity attenuation rate; at a high charge and discharge rate of 0.2-5C, the initial specific capacity at a rate of 5C is 635.7 mAh / g, and the capacity recovery rate reaches 95.65% when switched to 0.2C, indicating highly reversible electrochemical properties and showing good rate performance. Comparative Example 1

[0067] The difference between Comparative Example 1 and Example 1 is that the heating device in step (4) is different, the Joule heating device is replaced with a tube furnace, and the other steps remain unchanged. The specific operation is as follows:

[0068] 0.1 g of FeCo-ZIF-8 was placed in a tubular furnace and calcined under a nitrogen protective atmosphere at a calcination temperature of 1100°C and a heating rate of 5°C / min. The reaction was kept warm for 2 hours to obtain a carbon-supported FeCo diatomic porous lithium-sulfur battery composite material.

[0069] The obtained carbon-supported FeCo diatomic porous lithium-sulfur battery composite material was subjected to Raman spectroscopy test and N2-BET pore size distribution test, and the test results are shown in Table 1.

[0070] As shown in Table 1, the I D / I G The value and pore size range are 0.64, 3-45nm, I D / I G The pore size distribution is much smaller than 0.83 and 5-62 nm in Example 1, indicating that the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material prepared by the Joule heat treatment technology has more abundant carbon defects and multi-level pore structure. These defect sites can better anchor and disperse metal sites, and the multi-level pore structure is conducive to the adsorption of polysulfides, thereby showing higher catalytic activity and better stability. In addition, by comparing Comparative Example 1 with Example 1, it can be seen that the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material obtained by the Joule heat treatment technology has more carbon defects and multi-level pore structure, mainly relying on the rapid heating and cooling characteristics of the Joule heat treatment technology, which inhibits the disappearance of these carbon defects and multi-level pore structure.

[0071] The obtained carbon-supported FeCo diatomic porous lithium-sulfur battery composite material was used for lithium-sulfur battery testing. The testing method was the same as Example 1, and the test results are shown in Table 1.

[0072] It can be seen from Table 1 that the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material of Comparative Example 1 has a first-cycle discharge capacity of 557.37 mAh / g at a rate of 1C. After 700 cycles, the capacity retention rate is 50.25%, the initial specific capacity at 5C is 305.8 mAh / g, and the capacity recovery rate when switching from 5C to 0.2C is 85.5%, which is much smaller than the result of Example 1. Comparative Example 2

[0073] The difference between Comparative Example 2 and Example 1 is that no cobalt acetate is added in step (1), and the other steps remain unchanged, thereby obtaining a carbon-supported Fe single-atom porous lithium-sulfur battery composite material.

[0074] The obtained carbon-supported Fe single-atom porous lithium-sulfur battery composite material was subjected to Raman spectroscopy test and N2-BET pore size distribution test, and the test results are shown in Table 1.

[0075] As shown in Table 1, the I D / I G The value and pore size range are 0.71, 4-55nm, I D / I G The pore size distribution is much smaller than 0.83 and 5-62 nm in Example 1, indicating that the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material has richer carbon defects and a multi-level pore structure. These defect sites can better anchor and disperse metal sites, and the multi-level pore structure contributes to the adsorption of polysulfides, thereby exhibiting higher catalytic activity and better stability.

[0076] The obtained carbon-supported Fe single-atom porous lithium-sulfur battery composite material was used for lithium-sulfur battery testing. The testing method was the same as Example 1, and the test results are shown in Table 1.

[0077] As shown in Table 1, the carbon-supported Fe single-atom porous lithium-sulfur battery composite material of Comparative Example 2 has a first-cycle discharge capacity of 725.82 mAh / g at a rate of 1C. After 700 cycles, the capacity retention rate is 62.31%, the initial specific capacity at 5C is 420.8 mAh / g, and the capacity recovery rate at 5C switched to 0.2C is 90.5%, which is much smaller than the result of Example 1, indicating that cobalt acetate affects the electrochemical performance by affecting the carbon defect structure and multi-level pore structure. In addition, Co and Fe single atoms also have a synergistic effect, which enhances the interaction between polysulfides and active sites, thereby accelerating the conversion reaction kinetics of polysulfides and promoting the deposition of lithium sulfide, thereby improving the specific capacity and rate performance of lithium-sulfur batteries. Comparative Example 3

[0078] The difference between Comparative Example 3 and Example 1 is that no ferric acetate is added in step (1), and the other steps remain unchanged, thereby obtaining a carbon-supported Co single-atom porous lithium-sulfur battery composite material.

[0079] The obtained carbon-supported Co single-atom porous lithium-sulfur battery composite material was subjected to Raman spectroscopy test and N2-BET pore size distribution test, and the test results are shown in Table 1.

[0080] As shown in Table 1, the I D / I G The value and pore size range are 0.71, 4-55nm, I D / I GThe pore size distribution is much smaller than 0.83 and 5-62 nm in Example 1, indicating that the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material has richer carbon defects and a multi-level pore structure. These defect sites can better anchor and disperse metal sites, and the multi-level pore structure contributes to the adsorption of polysulfides, thereby exhibiting higher catalytic activity and better stability.

[0081] The obtained carbon-supported Co single-atom porous lithium-sulfur battery composite material was used for lithium-sulfur battery testing. The testing method was the same as Example 1, and the test results are shown in Table 1.

[0082] As shown in Table 1, the carbon-supported Co single-atom porous lithium-sulfur battery composite material of Comparative Example 3 has a first-cycle discharge capacity of 720.24 mAh / g at a rate of 1C. After 700 cycles, the capacity retention rate is 61.25%, the initial specific capacity at 5C is 419.7 mAh / g, and the capacity recovery rate when 5C is switched to 0.2C is 90.8%, which is much smaller than the result of Example 1, indicating that iron acetate affects the electrochemical performance by affecting the carbon defect structure and multi-level pore structure. In addition, Fe and Co single atoms also have a synergistic effect, which enhances the interaction between polysulfides and active sites, thereby accelerating the conversion reaction kinetics of polysulfides and promoting the deposition of lithium sulfide, thereby improving the specific capacity and rate performance of lithium-sulfur batteries. Comparative Example 4

[0083] The difference between Comparative Example 4 and Example 1 is that no ethyl acetate is added in step (2), and the other steps remain unchanged.

[0084] During the experiment, it was found that when ethyl acetate was not added, the precipitate and the liquid could not be separated after centrifugation, indicating that the addition of ethyl acetate helped to separate the solid and liquid and obtain FeCoZn-O nanoparticles, indicating that ethyl acetate is a key factor in obtaining FeCoZn-O nanoparticles.

[0085]

[0086] As can be seen from the above, compared with Comparative Example 1, the carbon-supported FeCo single-atom porous lithium-sulfur battery composite material prepared in Example 1 has a larger I D / I G Value(I D / I GThe larger the value, the more carbon defects there are) and the wider pore size distribution, which is mainly because the Joule heat treatment technology has the characteristics of rapid temperature rise and fall, which inhibits the disappearance of these defects and multi-level pore structures. Compared with Example 1, Comparative Examples 2-3 showed poor cycle stability and higher capacity decay rate under the same conditions; the main reasons for this performance advantage are as follows: FeCoZn-O nanoparticles react with 2-methylimidazole to generate FeCo-ZIF-8 in situ, in which the Co element mainly replaces the Zn site and coordinates with nitrogen, while the Fe element is mainly combined with oxygen and dispersed in ZIF-8. Due to the different coordination environments of the two elements Fe and Co and the uniform dispersion in the entire material, FeCo-ZIF-8 can be quickly prepared by Joule heat treatment technology to obtain a carbon-supported FeCo single-atom porous lithium-sulfur battery composite material with uniform element dispersion, which stimulates the synergistic effect between Fe and Co atoms, and then significantly enhances the interaction between polysulfide and active sites, thereby accelerating the conversion reaction kinetics of polysulfide and promoting the deposition of lithium sulfide, and improving the specific capacity and rate performance of lithium-sulfur batteries. In addition, ethyl acetate is a key factor in obtaining FeCoZn-O nanoparticles, and is also the key to preparing carbon-supported FeCo single-atom porous lithium-sulfur battery composite materials.

[0087] The above embodiments are intended to illustrate the essential content of the present invention, but are not intended to limit the protection scope of the present invention. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a carbon-supported FeCo diatomic porous lithium-sulfur battery composite material, characterized in that: The following steps are involved: (1) adding zinc acetate, cobalt acetate and ferric acetate into dimethyl sulfoxide to dissolve to obtain a first mixed solution; adding tetramethylammonium hydroxide into ethanol to dissolve to obtain a second mixed solution; (2) under stirring, adding the second mixed solution dropwise into the first mixed solution. After the addition is completed, stirring at room temperature for 5-10 minutes to obtain a third mixed solution; Adding ethyl acetate to the third mixed solution, centrifuging and vacuum drying to obtain FeCoZn-O nanoparticles; (3) preparing a mixed solvent of methanol and water, then adding FeCoZn-O nanoparticles and 2-methylimidazole into the mixed solvent, stirring and reacting at 40-80°C for 10-20h, centrifuging, washing, and vacuum drying to obtain FeCo-ZIF-8; (4) placing FeCo-ZIF-8 in the groove of the graphite sample stage of a Joule heating device, and then performing Joule heat treatment under a protective atmosphere of nitrogen or argon to obtain a carbon-supported FeCo diatomic porous lithium-sulfur battery composite material; In the step (1), the ratio of zinc acetate, cobalt acetate, iron acetate and dimethyl sulfoxide in the first mixed solution is: 1mmol: 0.02-0.04mmol: 0.03-0.06mmol: 20-30mL; the ratio of tetramethylammonium hydroxide and ethanol in the second mixed solution is 4-8mmol: 20mL; In the step (2), the volume ratio of ethyl acetate to the total solvent of dimethyl sulfoxide and ethanol in the third mixed solution is 0.4-0.6:

1.

2. The method for preparing the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material according to claim 1, characterized in that: In the step (2), the stirring speed is 100-300 r / min; the dropping time is 1-3 h; and the vacuum drying conditions are: drying temperature 50-80° C., and drying time 18-24 h.

3. The method for preparing the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material according to claim 1, characterized in that: In the step (3), the volume ratio of methanol to water in the mixed solvent is 1 mL:0.2-1 mL; the dosage ratio of FeCoZn-O nanoparticles, 2-methylimidazole, and the mixed solvent is 0.1 g:0.5-2 g:24-50 mL.

4. The method for preparing the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material according to claim 1, characterized in that: In the step (3), the washing conditions are: washing with deionized water and methanol three to five times respectively; the vacuum drying conditions are: drying temperature 50-80°C, drying time 5-10h.

5. The method for preparing the carbon-supported FeCo diatomic porous lithium-sulfur battery composite material according to claim 1, characterized in that: In the step (4), the conditions of the Joule heat treatment are: heat treatment temperature 700-1500°C, heating rate 1000-2500°C / s, and Joule heat treatment times 2-10 times.

6. An application of a carbon-supported FeCo diatomic porous lithium-sulfur battery composite material prepared by the preparation method according to any one of claims 1 to 5, characterized in that: Apply it to the positive electrode of lithium-sulfur batteries.

Citation Information

Patent Citations

  • Preparation method of CoNi bimetal organic framework derived carbon-sulfur composite material

    CN113054183A

  • FeCo double-monatomic modified nitrogen-doped porous carbon fiber, preparation method thereof and lithium-sulfur battery

    CN116960323A

  • Preparation method of sulfurized polyacrylonitrile positive electrode material for lithium-sulfur battery

    CN116960331A

  • Disclosed are lithium secondary battery and non-aqueous electrolyte solution used therein

    CN110061283A

  • Lithium-sulfur battery positive electrode material based on Zn / Co-ZIF derived composite carbon material and preparation method and application thereof

    CN116487575A